Ral GTPase promotes asymmetric Notch activation in the Drosophila eye in response to Frizzled/PCP signaling by repressing ligand-independent receptor activation. - Cho, B.; Fischer, J.A. (Development, 2011)
Ral is a small Ras-like GTPase that regulates membrane trafficking and signaling. Here, we show that in response to planar cell polarity (PCP) signals, Ral modulates asymmetric Notch signaling in the Drosophila eye. Specification of the initially equivalent R3/R4 photoreceptor precursor cells in each developing ommatidium occurs in response to a gradient of Frizzled (Fz) signaling. The cell with the most Fz signal (R3) activates the Notch receptor in the adjacent cell (R4) via the ligand Delta, resulting in R3/R4 cell determination and their asymmetric positions within the ommatidium. Two mechanisms have been proposed for ensuring that the cell with the most Fz activation sends the Delta signal: Fz-dependent transcriptional upregulation in R3 of genes that promote Delta signaling, and direct blockage of Notch receptor activation in R3 by localization of an activated Fz/Disheveled protein complex to the side of the plasma membrane adjacent to R4. Here, we discover a distinct mechanism for biasing the direction of Notch signaling that depends on Ral. Using genetic experiments in vivo, we show that, in direct response to Fz signaling, Ral transcription is upregulated in R3, and Ral represses ligand-independent activation of Notch in R3. Thus, prevention of ligand-independent Notch activation is not simply a constitutive process, but is a target for regulation by Ral during cell fate specification and pattern formation.